Investigation of aliphatic hydrocarbons in core sediments of Brunei Bay, East Malaysia - Pang, Swee Yun; Suhaimi, Suratman; Tay, Joo Hui; Norhayati, Mohd Tahir (Elsevier, 2021)
The distribution of aliphatic hydrocarbons in three sediment cores from Brunei Bay was investigated in order to understand their sources and the biogeochemical processes of these hydrocarbons. The total concentrations of C15 to C37 n-alkanes ranged from 0.70 to 16.5 μg g−1. Traces of hopanes with C29–C31 carbon homologs were detected in the study area. The carbon preference index (CPI15–37) ranged from 1.23 to 3.42 coupled with the natural n-alkane ratio (NAR19–32) ratios (1.52 to 5.34), and the presence of unresolved complex mixtures and hopanes, suggested slight contamination by anthropogenic hydrocarbons, presumably derived from activities along the coasts. The presence of C27 trisnorhopene and diploptene, as well as their association with long-chain and short-chain n-alkanes, revealed a depositional environment of organic matter in the sediment cores.